6p+3=2p+7

Simple and best practice solution for 6p+3=2p+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+3=2p+7 equation:


Simplifying
6p + 3 = 2p + 7

Reorder the terms:
3 + 6p = 2p + 7

Reorder the terms:
3 + 6p = 7 + 2p

Solving
3 + 6p = 7 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
3 + 6p + -2p = 7 + 2p + -2p

Combine like terms: 6p + -2p = 4p
3 + 4p = 7 + 2p + -2p

Combine like terms: 2p + -2p = 0
3 + 4p = 7 + 0
3 + 4p = 7

Add '-3' to each side of the equation.
3 + -3 + 4p = 7 + -3

Combine like terms: 3 + -3 = 0
0 + 4p = 7 + -3
4p = 7 + -3

Combine like terms: 7 + -3 = 4
4p = 4

Divide each side by '4'.
p = 1

Simplifying
p = 1

See similar equations:

| K-7=23 | | 4x+40=11x-10 | | (6j-7)=(3j+2) | | 8(3x-4)= | | 12x-15=8x+5 | | (x+3)=0 | | (9x-9y)+(44x+49y)= | | (2f+23)=(4f-5) | | 5x+8=-76-7x | | 5x-40=3x-15 | | (48x+77y)-(14x+34y)= | | 5(2m-7)=8 | | (m+12)=(3m-14) | | 118-3x=4x+20 | | .08x+.12(260-x)=.48x | | x+2+3(x-1)=1 | | 8m-5m=-25 | | 3(9x+14)+10x= | | 5(2x+2)+16= | | 2x^2=128 | | 6(3x+2)+2x= | | 2x^2=64 | | 8(4t+5)=19 | | 3x+15=67 | | 63f=945 | | 4x+6=55-3x | | N+5=12+n | | 19z=171 | | 4-x=-12 | | (x+1)(x+3)=0 | | 2t^3-14t^2=16t | | 8+3n=n-4 |

Equations solver categories